THE PROGRAM OF COMPLIANCE AS AN OBJECT OF TESTING IN THE CRIMINAL PROCESS AGAINST THE LEGAL PERSON - Espinoza Bonifaz, Renzo (2017)
The present article seeks to make known the probative treatment of compliance programs in a criminal proceeding followed against a legal entity. It is necessary to execute a compliance program within a company to achieve effective control and prevention of risks. It also details how the legal entity, in its status as a procedural subject, must prove the effectiveness of said compliance program in order to be exempt from liability for the commission of an offense carried out by a manager or subordinate belonging to the business organization.